Investigação da influência do atrito sobre as forças de forjamento no processo de recalque - Kussaba, Lika Livia (Universidade Federal de São Carlos, 2021)
Although it is a very old process, forging still has great significance until current days, being applied in numerous areas (automotive, aerospacial, tooling, and others). This variety is due to the characteristics found in forgings (high resistance, homogeneity, large-scale production possibilities, wide size range) along with material and finishing processes development. These part types are manufactured using different forging types, among which, upsetting can be pointed out as a very common process. Upsetting regards the reduction of the height of a simple-shaped part height resulting in its enlargement, in order to obtain a useful part. This paper studies the influence of lubricant usage in upsetting forging process. At first, the open die upsetting of a cylindrical billet was considered in order to validate the slice and finite elements simulation methods to get to the forging forces. Great correlation was obtained for all three friction-cases, however, a result of approximately 100 kN higher is observed for the maximum force obtained with finite elements simulation. This can be explained by the fact that non-friction situation cannot be reached by the software, therefore, it was adopted 0,0001 as friction coefficient instead of null. Afterwards, a study on upsetting process of a stepped shaft was conducted in three different situations, no lubricant usage, a mix of graphite and water as lubricant and salt solution as lubricant. Plotting the force per tooling distance curves for each case, great resemblance is observed in all three of them, except for the maximum force found, 13 MN for non-lubricated situation, 10 MN using water and graphite and 12,2 MN using salt solution.
Investigation of the influence of friction on the upsetter forging process forces
Keywords: Forjamento.; Método dos elementos finitos; Forging; Finite element Method; ENGENHARIAS::ENGENHARIA MECANICA::PROCESSOS DE FABRICACAO